Stres Akademik dalam Mengikuti Pembelajaran Jarak Jauh: Perbedaan Gender - Anisa Binta Nur Jannah; Ma'rifatin Indah Kholili; Rian Rokhmad Hidayat (Jurnal Psikoedukasi dan Konseling, 2022)
This study aims to determine the difference in academic stress levels of male and female students during distance learning. This research is descriptive comparative research. The subjects in this study were students of class XI at SMA Negeri in Surakarta. The research data were analyzed using the Independent Sample Test to determine whether there were differences in the academic stress levels of male and female students during distance learning. Based on the analysis results, male students had an average of 43.74, and female students experienced academic stress with an average of 47.27. The results of the Independent Sample Test show the value of Sig. 0.009 (0.009 <0.05), so this result indicated differences in the level of academic stress experienced by male and female students during distance learning.